2009
DOI: 10.1371/journal.pone.0007369
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Insecticidal Hammocks for Controlling Forest Malaria: A Community-Based Trial in a Rural Area of Central Vietnam

Abstract: BackgroundIn Vietnam, malaria remains a problem in some remote areas located along its international borders and in the central highlands, partly due to the bionomics of the local vector, mainly found in forested areas and less vulnerable to standard control measures. Long Lasting Insecticidal Hammocks (LLIH), a tailored and user-friendly tool for forest workers, may further contribute in reducing the malaria burden. Their effectiveness was tested in a large community-based intervention trial carried out in Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 7 publications
0
91
1
Order By: Relevance
“…This would involve the use of insect repellents, but these are prohibitively expensive for subsistence farmers, hunters, logging camp workers, and other rural people whose daily activities take them to the forest and forest fringe. The use of insecticideimpregnated hammocks has been successful for controlling forest malaria in Vietnam (143), but hammocks are not traditionally used in Malaysian Borneo, where most P. knowlesi cases occur, and so such a control measure would be difficult to implement successfully.…”
Section: Future Directions and Challengesmentioning
confidence: 99%
“…This would involve the use of insect repellents, but these are prohibitively expensive for subsistence farmers, hunters, logging camp workers, and other rural people whose daily activities take them to the forest and forest fringe. The use of insecticideimpregnated hammocks has been successful for controlling forest malaria in Vietnam (143), but hammocks are not traditionally used in Malaysian Borneo, where most P. knowlesi cases occur, and so such a control measure would be difficult to implement successfully.…”
Section: Future Directions and Challengesmentioning
confidence: 99%
“…The benefits of sleeping under LLINs need to be highlighted through education, and LLINs being made available through social marketing, as has been done for refugees from Afghanistan in Pakistan (Rowland and Nosten, 2001). Alternative approaches such as the provision of insecticide-treated hammocks for people frequenting forest areas in border areas (Magris et al, 2007;Thang et al, 2009), deltamethrin-sprayed tarpaulins or tents, and premethrin-treated blankets and top sheets provide more promising options for people overnighting in the forest (Graham et al, 2002;Rowland and Nosten, 2001). These protective measures achieve the goal of reducing exposure to infected vectors for populations who do not live in traditional housing each night, a feature common to people in border areas.…”
Section: Strengthening Of Preventive Measures For Cross-border Malariamentioning
confidence: 99%
“…The use of insecticide-treated hammock nets or long-lasting insecticidal hammocks has been shown to have protective efficacy against P. vivax and P. falciparum in South America (30) and in the Mekong region (31,32). In parts of Asia, the use of topical repellents, treated materials and treated clothing has been effective, especially when these measures are used in combination (33,34); however, other studies have found uncertainty about protective effects (32,35). In Ethiopia, the combined use of ITNs and repellents was found to be protective against both P. falciparum and P. vivax (36).…”
Section: Opportunitiesmentioning
confidence: 99%